Characteristics of the Cement Asphalt Emulsion Mixture With Early-Age Strength and Flowability - Tian, Yaogang; Yan, Xiaohui; Lu, Dong; Wang, Zhenjun; Zhang, Jun; Xu, Ouming; Li, Weiguang (Frontiers in Materials, 2020)
Cement asphalt emulsion mixture (CAEM) presents low early-age strength and poor flowability, which limits its application range at a certain degree. In this paper, CAEM with high early-age strength and flowability was proposed. The flowability, compressive strength, flexural strength of CAEM at different periods and 28d elastic modulus of CAEM were investigated. In addition, evolution of composition and microstructure of CAEM was analyzed by X-ray diffraction (XRD), scanning electronic microscope (SEM), and mercury intrusion porosimetry (MIP). The results indicated that the compressive strength of CAEM can be enhanced quickly in several hours. It could achieve 17-24MPa at 6h and almost reached 79%-90% of the 28d compressive strength. SEM and XRD analysis found that the hydration products in CAEM at different periods were obviously different. The hydration products of 2h filled the micro pores of the mixture. After 28d, the hydration products were connected to each other, resulting in a denser structure. The results of MIP analysis showed that the pore cumulative volume of CAEM was similar for 2h and 28d samples. These results testified that CAEM had high early-age strength.